HPV Genotype Distribution, Vaccine Protection Gaps, and Co-Infection Network Centrality Among 8515 Clinical Women in Wuxi, China: A Retrospective Cross-Sectional Study - Baocai Ran; Han Wu; Fengjuan Zhang (Vaccines, 2026)
Background/Objectives: Regional HPV genotype data for the Yangtze River Delta remain scarce, limiting evidence-based vaccine and screening policies. This study characterised the HPV genotype distribution, the vaccine protection gaps, and the co-infection network structure among clinical women in Wuxi, a prefecture-level city in the Yangtze River Delta region of Jiangsu Province, China. Methods: We retrospectively analysed all 8515 cervical HPV genotyping records from Xishan People’s Hospital of Wuxi City (January 2024–June 2025) using a 23-type fluorescent PCR panel classified by the International Agency for Research on Cancer (IARC) criteria. Results: The overall HPV prevalence was 22.83% (1944/8515; 95% CI 21.9–23.8%). The five leading types were HPV52 (4.82%), HPV58 (3.14%), HPV16 (2.96%), HPV53 (2.50%), and HPV42 (2.08%); HPV18 (0.74%) ranked below two unvaccinated carcinogens, HPV51 (1.76%, IARC Group 1) and HPV68 (1.68%, Group 2A). The age-stratified prevalence was U-shaped (χ2 = 123.27, p < 0.001), peaking at ≤20 years (52.94%; exploratory, n = 51) and ≥61 years (34.66%). Among the 1944 women with positive results, 43.0% were completely unprotected by the nonavalent vaccine, and 60.4% harboured at least one non-9vHPV type; HPV51 and HPV68 together accounted for 15.08% of the positive cases. In the co-infection network (n = 585 multiple-type infections), HPV52 achieved the highest degree centrality (281 co-infection events; normalised degree = 0.0218) and appeared in 8 of the 15 most frequent dual-type pairs, with observed/expected ratios of 6.5–14.8-fold. Conclusions: These findings reveal a clinically substantial vaccine protection gap and support the prioritisation of HPV51 and HPV68 in next-generation vaccine design.